2022
DOI: 10.1038/s41467-022-30704-x
|View full text |Cite
|
Sign up to set email alerts
|

Dosage-sensitive miRNAs trigger modulation of gene expression during genomic imbalance in maize

Abstract: The genomic imbalance caused by varying the dosage of individual chromosomes or chromosomal segments (aneuploidy) has more detrimental effects than altering the dosage of complete chromosome sets (ploidy). Previous analysis of maize (Zea mays) aneuploids revealed global modulation of gene expression both on the varied chromosome (cis) and the remainder of the genome (trans). However, little is known regarding the role of microRNAs (miRNAs) under genomic imbalance. Here, we report the impact of aneuploidy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 117 publications
1
19
0
Order By: Relevance
“…To address this question, global miRNA expression levels in the maize mature leaf tissue of a collection of maize aneuploid series containing various copies of chromosomal segments covering 82.1% of the maize W22 genome were examined in a recent study. [ 73–76 ] miRNAs for each aneuploid were partitioned into ones that are present on the varied chromosomal segment ( cis ) versus ones that are located in the remainder of the genome ( trans ). By comparing the miRNA expression levels in aneuploidy with the respective diploid or haploid control, the results showed that aneuploidy causes altered miRNA expression both in cis and in trans .…”
Section: Impact Of Aneuploidy and Polyploidy On Global Mirna Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…To address this question, global miRNA expression levels in the maize mature leaf tissue of a collection of maize aneuploid series containing various copies of chromosomal segments covering 82.1% of the maize W22 genome were examined in a recent study. [ 73–76 ] miRNAs for each aneuploid were partitioned into ones that are present on the varied chromosomal segment ( cis ) versus ones that are located in the remainder of the genome ( trans ). By comparing the miRNA expression levels in aneuploidy with the respective diploid or haploid control, the results showed that aneuploidy causes altered miRNA expression both in cis and in trans .…”
Section: Impact Of Aneuploidy and Polyploidy On Global Mirna Expressionmentioning
confidence: 99%
“…By comparing the miRNA expression levels in aneuploidy with the respective diploid or haploid control, the results showed that aneuploidy causes altered miRNA expression both in cis and in trans . [ 76 ] While the global trend of cis miRNA modulation could hardly be examined due to the limited number of cis miRNAs, trans miRNAs in different aneuploids exhibited a predominant trend of modulation toward the inverse level when assayed globally, although both positive and negative modulations were observed. In addition, results of differential miRNA expression analysis comparing tetrasomy to trisomy demonstrated that there are progressive cis and trans effects on a subset of miRNAs in aneuploids, with greater chromosomal dosage producing greater effects.…”
Section: Impact Of Aneuploidy and Polyploidy On Global Mirna Expressionmentioning
confidence: 99%
See 3 more Smart Citations